2012
DOI: 10.1074/mcp.m112.020057
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry–based Proteomic Analysis of the Matrix Microenvironment in Pluripotent Stem Cell Culture

Abstract: The cellular microenvironment comprises soluble factors, support cells, and components of the extracellular matrix (ECM) that combine to regulate cellular behavior. Pluripotent stem cells utilize interactions between support cells and soluble factors in the microenvironment to assist in the maintenance of self-renewal and the process of differentiation. However, the ECM also plays a significant role in shaping the behavior of human pluripotent stem cells, including embryonic stem cells (hESCs) and induced plur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 60 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…6,10 The results of the present study demonstrated the organization-and lineage-specific characteristics of ESC-derived ECMs and their differential signaling capacity in regulating ESC fate.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…6,10 The results of the present study demonstrated the organization-and lineage-specific characteristics of ESC-derived ECMs and their differential signaling capacity in regulating ESC fate.…”
Section: Discussionmentioning
confidence: 81%
“…26 Parallel to the organizational dependence, the characteristics of PSC-derived ECMs are also influenced by lineage specifications. 6,23,29 For example, cerberus, a small antagonist of bone morphogenetic protein (BMP), was detected in the secretome and ECMs of ESCs undergoing cardiac differentiation, but not neural differentiation. 6,28 Finally, the ECMs derived at the early or late stage of EBs exhibited different signaling capacities, suggesting the influence of the developmental stage on ECM characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations